Understanding fractions (Understanding mathematics v2.0)
The objective of this series of 9 products is to provide a resource for teaching and learning mathematics at Key Stages 2 and 3 and for Application of Number. Students of many other mathematics courses will find the resources valuable. The products aim to provide a highly structured approach to learning where the student is guided step-by-step through each concept in a topic. At every stage the student has to interact with the computer in completing questions and examples and they are unable to proceed until satisfactory answers have been provided. When students enter incorrect answers the programs will give hints on the correct answer where appropriate. The programs make extensive use of animated graphics to help students understand mathematical concepts. The programs stress the use of correct mathematical language and terminology and how these link to mathematical symbols. This approach ensures that students understand one topic before proceeding to the next. Accompanying worksheets are used to provide a structure to students work whilst on the computer and also to provide further activities off the computer. The whole package is designed to give students confidence in learning mathematics and teachers confidence in their students ability.